4x(x-3y)+12y(3y-x)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(x^3+2x^2-2x-1\)
\(=\left(x-1\right)\left(x^2+x+1\right)+2x\left(x-1\right)\)
\(=\left(x-1\right)\left(x^2+3x+1\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
3: \(x^3+3x^2-16x-48\)
\(=x^2\left(x+3\right)-16\left(x+3\right)\)
\(=\left(x+3\right)\left(x-4\right)\left(x+4\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a. \(-x^2+4x+y^2-12y+47\)
\(=-\left(x^2-4x-y^2+17y-47\right)\)
\(=-\left[x^2-4x+4-\left(y^2-12y+36\right)-15\right]\)
\(=-\left[\left(x-2\right)^2-\left(y-6\right)^2-15\right]\)
Vì \(\left(x-2\right)^2-\left(y-6\right)^2-15\ge-15\forall x\)
\(\Rightarrow-\left[\left(x-2\right)^2-\left(y-6\right)^2-15\right]\le15\)
Vậy GTLN của bt trên là 15 \(\Leftrightarrow x=2;y=6\)
b. \(-x^2-x-y^2-3y+13\)
\(=\frac{1}{4}\left(-4x^2-4x-4y^2-12y+52\right)\)
\(=\frac{1}{4}\left[-\left(2x+1\right)^2-\left(2y+3\right)^2+42\right]\)
Vì \(\frac{1}{4}\left[-\left(2x+1\right)^2-\left(2y+3\right)^2+42\right]\le42\forall x;y\)
\(\Rightarrow-\left(2x+1\right)^2-\left(2y+3\right)^2+42\le\frac{21}{2}\forall x;y\)
Vậy GTLN của bt trên là 21/2 \(\Leftrightarrow x=-\frac{1}{2};y=-\frac{3}{2}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(x+3y\right)^2-\left(2x-3y\right)^2-2x^2+12y^2\)
\(=x^2+2\cdot x\cdot3y+\left(3y\right)^2-\left[\left(2x\right)^2-2\cdot2x\cdot3y+\left(3y\right)^2\right]-2x^2+12y^2\)
\(=x^2+6xy+9y^2-4x^2+12xy-9y^2-2x^2+12y^2\)
\(=-5x^2+18xy+12y^2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Lời giải:
1.
$x^3+3x^2-16x-48=(x^3+3x^2)-(16x+48)=x^2(x+3)-16(x+3)$
$=(x+3)(x^2-16)=(x+3)(x-4)(x+4)$
2.
$4x(x-3y)+12y(3y-x)=4x(x-3y)-12y(x-3y)=(x-3y)(4x-12y)=4(x-3y)(x-3y)=4(x-3y)^2$
3.
$x^3+2x^2-2x-1=(x^3-x^2)+(3x^2-3x)+(x-1)=x^2(x-1)+3x(x-1)+(x-1)$
$=(x-1)(x^2+3x+1)$
4x(x-3y)+12y(3y-x)
=4x2-12xy+36y2-12xy
=4x2-12xy-12xy+36y2
=4x2-24xy+36y2
\(4x\left(x-3y\right)+12y\left(3y-x\right)\)
\(=4x^2-12xy+36y^2-12xy\)
\(=4x^2+36y^2-\left(12xy+12xy\right)\)
\(=4x^2+36y^2-24xy\)